Creating Process of Composition Of The “Kulino” Musical Drama At Theater Aura Indonesia - Darussalam, Najwa Leonita; Wiyoso, Joko (Universitas Negeri Semarang, 2021)
Music for the Aura Theater is not only a supporter of the presentation of the show, but also as a medium for conveying the core story in a performance that is packaged in the form of songs and becomes part of the storyline. This makes researchers interested in the process of creating songs in their musical dramas. This study aims to identify and describe the process of creating compositions for musical drama songs in Kulino scripts at the Aura Indonesia Theater performance. This study uses a qualitative descriptive method that produces descriptive data. The research location is in the center of theatrical activities of Theater Aura Indonesia with data sources from the chairman as well as the director of Kulino performances and composers. Data were collected by using observation, interview, and documentation techniques. The data analysis technique used in this study is an interactive model whose elements include data reduction, data presentation, and conclusions. The results showed that in the process of creating the composition of the Kulino musical drama song through stages (1) script review, namely the activities of appreciating, reviewing, discussing, or reviewing all the elements contained in the script to be worked on (2) observation, namely the stages carried out by the composer. to get musical inspiration which is then illustrated in the form of rough notes (3) pouring, namely pouring rough notes from observations into the form of musical compositions (4) embodiment, namely redeveloping the finished song by adding other musical instruments, namely keyboard, guitar melody, violin, cello, drum, bass, flute, and saxophone (5) presentation, in which the composer presents the finished song to the director and assistant director.